2019
DOI: 10.1200/jgo.19.00174
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Predictive Biomarkers in Patients With Lung Adenocarcinoma From Southern Brazil Reveals a Distinct Profile From Other Regions of the Country

Abstract: PURPOSE Adenocarcinoma is the most common histologic subtype of non–small-cell lung cancer, representing 40% of all diagnoses. Several biomarkers are currently used to determine patient eligibility for targeted treatments, including analysis of molecular alterations in EGFR and ALK, as well as programmed death-ligand 1 (PD-L1) protein expression. Epidemiologic data reporting the frequency of these biomarkers in Brazilian patients with lung adenocarcinoma (LUAD) are limited, and existing studies predominantly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 50 publications
2
21
1
Order By: Relevance
“…This lower frequency of KRAS mutations could be a result of a lower frequency of smokers in that cohort and a high EGFR mutation frequency, as the two mutation types are usually mutually exclusive. In the Brazilian population, KRAS mutation frequencies of 14.6-30.2% have been reported (12,13,26,27). These differences could be partially explained by differences in detection methods and population characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…This lower frequency of KRAS mutations could be a result of a lower frequency of smokers in that cohort and a high EGFR mutation frequency, as the two mutation types are usually mutually exclusive. In the Brazilian population, KRAS mutation frequencies of 14.6-30.2% have been reported (12,13,26,27). These differences could be partially explained by differences in detection methods and population characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we identified seven LUAD tumors harboring the founder TP53 variant among 586 samples recruited from patients in southern Brazil, a cohort described in detail elsewhere ( Andreis et al, 2019 ). Remarkably, all variant-positive tumors were diagnosed over age 50 years.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 586 LC samples derived from a cohort described in a previous study from our group ( Andreis et al, 2019 ) were analyzed. Patients were originally recruited for somatic mutation testing in EGFR (exons 18–21), KRAS (exons 2 and 3), BRAF (exons 11 and 15), and NRAS (exons 2 and 3) genes from different hospitals and clinics distributed in 22 healthcare centers located in the three states of the southern region of Brazil: Rio Grande do Sul ( N = 496), Santa Catarina ( N = 20), and Paraná ( N = 70).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…TCGA comprehensively mapped mutations and transcriptome changes, as well as their frequency in large sample sets of lung AD and SCC, and demonstrated that mutations in oncogenes such as EGFR, K-RAS, ALK and BRAF occur in >60% of lung AD cases [7], with driver mutations targetable by tyrosine kinase inhibitors [8]. The frequency of alterations of these driver genes in the Brazilian population is slightly different and associated with a genetic ancestry admixture [9][10][11]. Although the development of molecularly targeted therapies including EGFR tyrosine kinase inhibitors have benefited only a small fraction (15%) of patients with lung AD.…”
Section: Introductionmentioning
confidence: 99%